2006
DOI: 10.1159/000097818
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effect of Carvedilol on Professional Phagocytes

Abstract: Aim: Superfluous reactive nitrogen and oxygen species generation is implicated in the damage of tissues at sites of inflammation where activated neutrophils and macrophages are involved. This study was conducted to investigate whether the beneficial effects of carvedilol involve modulation of respiratory burst, degranulation-myeloperoxidase release and inducible nitric oxide synthase (iNOS) expression. Methods: Spectrophotometry and chemiluminescence were used to evaluate the effect of carvedilol on opsonized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
0
14
0
1
Order By: Relevance
“…Luminol (10 -5 M) served as a marker LDCL. Luminescence of this agent is nonselective to oxygen-containing radicals [13]. The results were recorded on a Guardian liquid scintillation counter (Wallac) for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…Luminol (10 -5 M) served as a marker LDCL. Luminescence of this agent is nonselective to oxygen-containing radicals [13]. The results were recorded on a Guardian liquid scintillation counter (Wallac) for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…In addittion, one in vivo study using rats indicated that the drug decreased arterial pressure whilst it increased NO production [82]. On the other side, Pecivova et al reported that carvedilol does not affect the expression of iNOS by macrophages [83] and Yoshioka et al, (2000) demonstrated a novel effect of carvedilol as a NO quenching agent. Their results indicate that carvedilol directly interacts with NO in a cell-free system [84].…”
Section: No In Chf-effects Of Carvedilolmentioning
confidence: 99%
“…The development of pharmacological procedures to ameliorate undesirable ROS production may become one of the central issues in research on aging and oxidative stress-related diseases in the near future. A number of therapeutically used medicaments and natural products acted not only as extracellular scavengers but they also suppressed intracellular formation of ROS in human neutrophils (Drábiková et al 2006, 2013, Jančinová et al 2012a,b, 2015, Nosáľ et al 2006, Pečivová et al 2007. Since the optimum therapy is expected to minimize tissue damage without reduction of neutrophil physiological function, separate analysis of extra-and intracellular effects of antioxidants is of particular importance (El-Benna et al 2010).…”
Section: Introductionmentioning
confidence: 99%